Characterization of the upstream region of the formate dehydrogenase operon of Methanobacterium formicicum. - Patel, P S (1988)
The fdhA and fdhB genes of Methanobacterium formicicum, which code for the alpha and beta subunits of formate dehydrogenase, were cotranscribed as part of a large transcript. By using Northern (RNA) gel blot analysis, the transcription start site was located within a 1.6-kilobase BglII-NcoI fragment 4.3 kilobases upstream from the fdhA gene. The precise transcription start site within the fragment was determined with the aid of primer extension analysis and S1 nuclease protection studies. A putative promoter sequence for structural genes of methanogenic archaebacteria is proposed based on a comparison of DNA sequences of the upstream region of methanogen operons for which transcription initiation sites are known. Comparison of the DNA sequence of the upstream region of the fdh operon of M. formicicum with the sequence upstream of the fdhF gene of Escherichia coli revealed regions of considerable identity.